Comparison of Blood Gas Analysis between Benchtop and Handheld Device - Phey Liana; Iza Netiasa Haris; Yan Effendi Hasyim (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
The use of blood gas analysis is to determine the Acid-base status required to treat patients with emergency conditionssuch as metabolic disorders and respiratory diseases. Benchtop device is commonly used in hospitals to analyze blood gas;however, handheld devices are recently more often used in emergency settings due to its quick and simple process. Thisstudy was performed to compare blood gas analysis results between the i-STAT handheld device and the Nova pHox Ultrabenchtop device that were currently being used in the central laboratory. This cross-sectional study was conducted by using42 arterial blood patients that were measured with i-STAT handheld device dan Nova pHox Ultra benchtop device. The pH,pCO2, and pO2 parameters were then evaluated. The data were analyzed using Spearman's correlation test, Mann-Whitneytest, and Bland-Altman plots. This study showed a very strong positive correlation for all parameters. Mann-Whitneycomparison test showed that there was no significant difference between the result of the two devices (p-value > 0.05). Allparameters showed that 95% of plots were within the acceptable limit. There was no clinical significance on the mean biasesof blood gas results between both devices. The i-STAT and Nova pHox Ultra devices showed a good agreement for bloodgas measurement. Therefore, both devices can be used interchangeably with minimal effect on clinical decision-making.